Artificial neural network data fusion-mediated dual-mode sensor based on Fe3O4@PdIr for Salmonella typhimurium detection in food - Mengxia Duan; Wenxiu Zheng; Zepeng Gu; Man Ding; Shiping Luo; Zhouping Wang; Shijia Wu; Yukun Huang; Nuo Duan (Food Research International, 2026)

PdIr bimetallic nanozyme engineered metal-organic frameworks integrated dual-mode sensor toward Stx2 detection in food - Mengxia Duan; Minghui Lu; Man Ding; Zhouping Wang; Shijia Wu; Nuo Duan (Food Chemistry, 2026)

Interface-enhanced label-free FeOOH-mesoporous TiO2 nanocomposite biosensor for highly sensitive quantitative exosome detection to assist cancer screening - Bokai Zhou; Shuyan Liu; Xu Yin; Jie Feng; Mengyu Ding; Caiwei Hu; Guanghai Piao; Ji Man Kim; Junjie Piao; Yu Bai; Mingshi Jin (Analytica Chimica Acta, 2026)

PD-1/PD-L1 inhibition after cryoablation is associated with improved tumor control and immunosuppressive microenvironment remodeling in Lewis lung adenocarcinoma - Qi Liu; Shuo Zhang; Xuxin Chen; Jiao Li; Man Qi; Yongqun Li; Yiwei Ding; Xiaoyu Zhao; Jun Shi; Jiajia Tang; Meng Liu; Xue Wang; et al. (Cryobiology, 2026)

Signal hijacking and ROS attack antibacterial strategy using QS-interfering aptamer and bimetallic MOF - Kuaile Wu; Mengxia Duan; Yalin Mo; Man Ding; Ning Ma; Zhouping Wang; Shijia Wu; Nuo Duan (Chemical Engineering Journal, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Endothelial VEGFR2 insufficiency promotes the transition of lymphatic to hematopoietic transcriptional programs - Taotao Li; Xudong Cao; Fei Zhou; Xiujuan Li; Wenjuan Ma; Xiuyan Zhang; Haoyu Zhong; Beibei Xu; Man Chu; Xiwen Jia; Kai Ding; Xin Shen; et al. (Angiogenesis, 2026)

Aptamer-functionalized PVA/AG hydrogel for enrofloxacin detection in milk with simplified sample pretreatment - Meihua Dong; Zhuowen Deng; Man Ding; Nuo Duan; Zhouping Wang; Shijia Wu (Food Chemistry, 2026)

Trophic transfer and toxicity of 6PPD-quinone in an aquatic food chain: Role of uptake routes - Min Lv; Xinlei Wang; Mingsan Man; Xiaotong Guo; Xianbo Chang; Dawei Shi; Lingxin Chen; Xiaoyong Yang; Jing Ding (Journal of Environmental Chemical Engineering, 2026)

A physically constrained and interpretable deep learning framework for PM2.5 inversion under sparse monitoring conditions in arid regions - Xinyue Zhang; Wen Ma; Jianli Ding; Pai Peng; Hongru Wang; Qianqian Man; Yanyi Yang; Nan Du (Environmental Pollution, 2026)

Epigenetic impacts of the acaricide flumethrin on honeybees (Apis mellifera) - Xue Wang; Suzhen Qi; Mu Ding; Wei Zhang; Aidi Huang; Changlu Sun; Man Fan; Liming Wu; Miao Wang (Environmental Pollution, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Different environmental controls on archaeal and bacterial GDGT distributions in Chinese peatlands - Huan Yang; Lijia Zhang; Weihua Ding; Zhengyu Xia; Yi Man; Linfeng Gong; Xianyu Huang; Xinyue Dang; Jiachen Fan; Jie Wu; Miao Huang (Organic Geochemistry, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Evaluating 6PPD-Q bioavailability and biotransformation in zebrafish by diffusive gradients in thin-films - Suyu Ren; Yuxiang Xia; Mengfei Wang; Sijia Zhao; Xiao Wu; Mingsan Man; Yize Du; Qixia Yang; Min Lv; Lingxin Chen; Jing Ding (Environmental Research, 2026)

Multi-media distribution, partitioning, and risks of tire additives and their transformation products in coastal waters of China - Chao Liu; Shuang Lu; Min Lv; Longwen Fu; Mingsan Man; Yize Du; Jing Ding; Wei Liu; Lingxin Chen (Marine Pollution Bulletin, 2026)

Earthworms enhance soil phosphorus cycling but plant responses differ among earthworm ecological categories: a meta-analysis - Ziyue Wang; Man Liu; Wenli Ding; Zhihui Chang; Benjamin L. Turner; Hans Lambers (Soil Biology and Biochemistry, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Metal nanoparticles transport in the subsurface: a review - Quan Wan; Miaoyue Zhang; Man Zhao; Erwin Klumpp; Roland Bol; Kengbo Ding; Zhuobiao Ni; Jingjing Li; Chao Jin; Rongliang Qiu (Environmental Chemistry Letters, 2026)

Rational engineering of a polyvalent aptamer for mitigating Aflatoxin B1 toxicity by disrupting metabolite Aflatoxin B1-8, 9-epoxide formation - Yuting Chang; Tingting Su; Mengxia Duan; Man Ding; Kuaile Wu; Zhouping Wang; Shijia Wu; Nuo Duan (Journal of Hazardous Materials, 2026)

Clathrin-mediated endocytosis governs CdS nanoparticle internalization in rice (Oryza sativa L.) roots - Xinxing Nie; Yili Luo; Langlang Li; Lijuan Xie; Qingqi Lin; Chao Jin; Man Zhao; Kengbo Ding; Hua Qi; Rongliang Qiu (Journal of Hazardous Materials, 2025)

Integrating multifunctional FePOs@CeO2 with colorimetric electrochemical activity and structurally optimized aptamer for precise detection of amoxicillin - Mengxia Duan; Hong Xu; Dichen Ying; Man Ding; Zhouping Wang; Shijia Wu; Nuo Duan (Food Bioscience, 2025)

Insights into the multi-media spatiotemporal distribution, partitioning, and risks of pharmaceuticals and personal care products in the southern Bohai Sea - Shuang Lu; Han Chen; Min Lv; Peng Zhang; Longwen Fu; Mingsan Man; Wei Zhang; Dongliang Wang; Jing Ding; Wei Liu; Lingxin Chen (Journal of Environmental Management, 2025)

Unraveling the mysteries of food allergens: aptamer-driven detection and suppression strategies - Man Ding; Mengxia Duan; Shijia Wu; Nuo Duan (Food Research International, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Ultra-sensitive detection of Cu2+ in water and infant formula using a carbon dot-embedded MIL-53 electrochemiluminescence sensor - Xiaofeng Wei; Yu Su; Man Jiang; Hongfei Ji; Ruizhong Zhang; Daqian Song; Lan Ding; Yanhua Chen (Food Chemistry, 2025)

Impact of low-voltage alternating electric field on the chemical and sensory profiles of mulberry wine: Analysis of antioxidant activity and volatile compounds - Qiudi Zhu; Xinwei Lu; Chenxi Ding; Shuang Xian; Xingyan Liu; Zhiqing Zhang; Man Zhou; Zhiqin Zheng; Bin Guo; Anjun Chen (Food Bioscience, 2025)

Theoretical analysis and design method of CFRP-strengthened inclined welded steel plates with initial cracks under fatigue loadings - Lili Hu; Xinyu Ding; Lingzhen Li; Man-Tai Chen; Peng Feng (Engineering Structures, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

High-resolution estimation of urban anthropogenic carbon emissions - Zirong Lin; Bo Huang; Jia He; Yizhen Yan; Man Xiao; Qinrui Luo; Zhulin Qi; Xiaotian Ding (Sustainable Cities and Society, 2025)

Applicability analysis of different evapotranspiration models for maize farmland in the lower Yellow River Plain based on eddy covariance measurements - Xiaojuan Ren; Guodong Li; Shengyan Ding; Jingyu Wang; Man Zhang; Xuejian Sun; Qingtao Zhao; Pengfei Li (Ecohydrology & Hydrobiology, 2025)

Stearic acid-modified magnetic porous hydroxyapatite microspheres for efficient marine oil spill treatment - Wanying Ding; Man Liu; Yuanhao Xing; Dan Tie; Zheng Chen; Jiazhen Li; Li Chen; Jingdi Chen; Panpan Pan (Journal of Environmental Chemical Engineering, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Unveiling multimodal consolidation process of the newly reclaimed HKIA 3rd runway from satellite SAR interferometry, ICA analytics and Terzaghi consolidation theory - Zhuo Jiang; Guoqiang Shi; Songbo Wu; Xiaoli Ding; Chaoying Zhao; Man Sing Wong; Zhong Lu (Remote Sensing of Environment, 2025)

SERS sensor based on an optimized specific aptamer by Capture-SELEX screening for rimantadine detection - Mengxia Duan; Man Ding; Wenxiu Zheng; Jin Li; Zhouping Wang; Shijia Wu; Nuo Duan (Food Bioscience, 2025)

Size-specific mediation of the physiological responses and degradation ability of microalgae to sulfamerazine by microplastics - Xinlei Wang; Min Lv; Jin Liu; Mingtao Ba; Mingsan Man; Kun Yin; Jing Ding; Xianbo Chang; Lingxin Chen (Aquatic Toxicology, 2025)

CSF multi-omics of intracerebral hemorrhage from onset to reperfusion underscores lipid metabolism in functional outcome - Yibin Jiang; Sin Man Lam; Shuixian Zhang; Huan Miao; Yong Zhou; Qian Zhang; Tengyuan Zhou; Hui Feng; Ning Ding; Haomiao Wang; Ran Luo; Yi Yin; et al. (Science Bulletin, 2025)

Enhanced detection of 4-nitrophenol in drinking water: ECL sensor utilizing velvet-like graphitic carbon nitride and molecular imprinting - Rui Xu; Yu Su; Hongfei Ji; Man Jiang; Ruizhong Zhang; Lan Ding; Yanhua Chen; Daqian Song (Food Chemistry, 2024)

A Review of Life Cycle Assessment of Soil Remediation Technology: Method Applications and Technological Characteristics - Ning Ding; Xianhao Meng; Zhan Zhang; Jin Ma; Yongping Shan; Zhong Zhong; Haibo Yu; Man Li; Wentao Jiao (Reviews of Environmental Contamination and Toxicology, 2024)

Development and application of diffusive gradients in thin-films for in-situ monitoring of 6PPD-Quinone in urban waters - Suyu Ren; Yuxiang Xia; Xinlei Wang; Yangquan Zou; Zhenping Li; Mingsan Man; Qixia Yang; Min Lv; Jing Ding; Lingxin Chen (Water Research, 2024)

A CREAM model optimization method based on fatigue testing experiments and machine learning techniques for maritime transportation applications - Huining Pei; Hao Gong; Man Ding; Yujie Ma; Ziyu Wang; Qi Xin (Ocean Engineering, 2024)

Preparation of enzymatic hydrolysates of mulberry leaf flavonoids and investigation into its treatment and mechanism for zebrafish inflammatory bowel disease - Dongsheng Jia; Xi Tian; Yuting Chen; Jie Liu; Man Wang; Zhangsen Hao; Changshun Wang; Ding Zhao (Fish & Shellfish Immunology, 2024)

Multi-constraint improved RS path planning method for unmanned rice direct seeding machine - Lian Hu; Kang Hou; Jie He; Zhongxian Man; Jiasheng Xie; Pei Wang; Tuanpeng Tu; Ruitao Gao; Le Zi; Yufeng Huang; Mingjin Li; Shuaiqi Ding; et al. (Computers and Electronics in Agriculture, 2024)

Integration of engineering microbial consortium and boosting extracellular amylase of B. amyloliquefaciens for intensifying bioconversion of food waste into lipopeptides - Jia-Xuan He; Zheng-Jie Hou; Bin Qiao; Ming-Zhu Ding; Chun-Yang Cao; Yu-Miao Zhang; Qiu-Man Xu; Jing-Sheng Cheng (Journal of Environmental Chemical Engineering, 2024)

In-situ biogenic FeS boosted acetate accumulation through CO2 capture and valorization using microbial electrosynthesis (MES) - Huixing Wu; Lingyan Ding; Han Wang; Shuaishuai Man; JunRae Kim; Liwei Qiu; Qun Yan (Chemical Engineering Journal, 2024)

Aging increases the particulate- and leachate-induced toxicity of tire wear particles to microalgae - Min Lv; Fanyu Meng; Mingsan Man; Shuang Lu; Suyu Ren; Xiaoyong Yang; Qiaoning Wang; Lingxin Chen; Jing Ding (Water Research, 2024)

Reinforcing the efficiency of photocatalytic CO2 conversion with H2O vapor through the integration of photothermal Cu/C@Bi/C supported on 3D g-C3N4 under full-spectrum solar irradiation - Yanan Wang; Jiayu Ding; Qi Yin; Cheng Zhang; Yiqing Zeng; Song Xu; Qian Liang; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2024)

Huge redshift of absorption edge in a novel Z-type Bi2Sn2O7/α-Bi2O3 junction for highly efficiently visible light degradation of norfloxacin and bisphenol AF - Man Yu; Kaitian Zuo; Bangfu Ding; Shukai Zheng; Lei Zhang; Liang Mao; Junying Zhang (Journal of Environmental Chemical Engineering, 2024)

Recent advances in the bovine β-casein gene mutants on functional characteristics and nutritional health of dairy products: Status, challenges, and prospects - Yilin Sun; Yixin Ding; Biqi Liu; Jinfeng Guo; Yue Su; Xinyan Yang; Chaoxin Man; Yu Zhang; Yujun Jiang (Food Chemistry, 2024)

Unveiling the urban resilience in cities of China, a study on NO2 concentrations and COVID-19 pandemic - Shaolin Wu; Man Sing Wong; Baofeng Di; Xiaoli Ding; Guoqiang Shi; Edwin H.W. Chan; Waqas Muhammad (Atmospheric Environment, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Improving salt-tolerant artificial consortium of Bacillus amyloliquefaciens for bioconverting food waste to lipopeptides - Yu-Miao Zhang; Bin Qiao; Wei Shang; Ming-Zhu Ding; Qiu-Man Xu; Tian-Xu Duan; Jing-Sheng Cheng (Waste Management, 2024)

Comprehensive kinetic modeling and product distribution for pyrolysis of pulp and paper mill sludge - Fangjun Chen; Lei Ding; Yongfeng Zhu; Guanlong Ren; Yi Man; Kun Hong; Lin Lang; Henrik Ström; Qingang Xiong (Science of The Total Environment, 2024)

Over 30% external quantum efficiency for doping-free D-A-type thermally activated delayed fluorescence organic light-emitting diodes - Yang Li; Yixia Liu; Yang Gao; Kai Zhang; Yan-Qiu Sun; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2024)

One-pot chitin pulping using recyclable superbase-based protic ionic liquid - Qingqing Tao; Felipe Nunes Henriquez; Kang Ding; Wai Lun Man; Matthew Y. Lui (Carbohydrate Polymers, 2024)

Impact of mineral dust photocatalytic heterogeneous chemistry on the formation of the sulfate and nitrate: A modelling study over East Asia - Xiao Li; Zechen Yu; Man Yue; Yaman Liu; Kan Huang; Xuguang Chi; Wei Nie; Aijun Ding; Xinyi Dong; Minghuai Wang (Atmospheric Environment, 2024)

Research on improving the accuracy of laser-induced breakdown spectroscopy analysis by considering plasma attenuation rate characteristics - Chao Li; Zhengjiang Ding; Tao Zhang; Zhongyi Bao; Meili Guo; Man Wang; Yunfeng Bi (Analytica Chimica Acta, 2024)

A new exploration of the “Three Lines One Permit” policy: Marine zoning strategy based on land-sea coordination - Yingxian Long; Wen Zhou; Man Hong; Di Zhao; Ding Wen; Yuhuan Zhang; Xi Deng (Environmental Impact Assessment Review, 2023)

Profiling of the spatiotemporal distribution, risks, and prioritization of pharmaceuticals and personal care products in coastal waters of the northern Yellow Sea, China - Xiaotong Guo; Min Lv; Lehui Song; Jing Ding; Mingsan Man; Longwen Fu; Shuang Lu; Lijun Hou; Lingxin Chen (Journal of Hazardous Materials, 2023)

Thienoacene-fused fluorophores for highly efficient deep red/near-infrared OLEDs - Li Zhu; Yixia Liu; Xiaofei Wang; Kai Zhang; Jing-Wen Tai; Yan-Qiu Sun; Chuan-Kui Wang; Lei Ding; Man-Keung Fung; Jian Fan (Chemical Engineering Journal, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

Terpenoids of quinoa bran suppresses colorectal cancer by inducing cell apoptosis - Man Ding; Xuechen Zhang; Jiangying Shi; Kaili Cui; Ruipeng Yang; Fengming Liu; Shuhua Shan; Ghani Israr; Zhuoyu Li (Food Bioscience, 2023)

Conjugated microporous polyimide cathodes for sodium/lithium-ion batteries with ultra-long cycling performance - Lei Chen; Yuke Li; Xuefan Wang; Juncheng Wu; Yijiao Ding; Shi-Bin Ren; Li Zhang; Zhenwei Xu; Bingwei Chen; De-Man Han; Ying-peng Wu (Chemical Engineering Journal, 2023)

Novel incomplete phase transition from α-Bi2O3 to γ-Bi2O3 constructing dual interfaces contacts with BaTiO3 for highly efficient degradation of antibiotics - Man Yu; Bangfu Ding; Jiawei Wu; Shun Zheng; Xin Qian; Lei Zhang; Shukai Zheng; Liang Mao; Junying Zhang (Chemical Engineering Journal, 2023)

Under-loaded operation of an anaerobic-anoxic-aerobic system in dry and wet weather dynamics to prevent overflow pollution: Impacts on process performance and microbial community - Lu-Man Jiang; Zhenjian Zhang; Yunhui Li; Jialei Xu; Kun Wang; Xinya Ding; Junli He; Zhan Qiu; Hua Zhou; Zhen Zhou (Bioresource Technology, 2023)

Overview of structure, function and integrated utilization of marine shell - Meiqi Cheng; Man Liu; Lirong Chang; Qing Liu; Chunxiao Wang; Le Hu; Ziyue Zhang; Wanying Ding; Li Chen; Sihan Guo; Zhi Qi; Panpan Pan; et al. (Science of The Total Environment, 2023)

Restored vegetation is more resistant to extreme drought events than natural vegetation in Southwest China - Ying Liu; Zhi Ding; Yanan Chen; Fengqin Yan; Pujia Yu; Weidong Man; Mingyue Liu; He Li; Xuguang Tang (Science of The Total Environment, 2023)

Three-dimensional numerical study of cooling water discharge of Daya Bay Nuclear Power Plant in southern coast of China during summer - Bingxu Geng; Lingyan Lu; Qian Cao; Wen Zhou; Shiyu Li; Ding Wen; Man Hong (Frontiers in Marine Science, 2023)
The impact of thermal pollution caused by cooling water discharge of power plant on the surrounding marine ecology has been a hot issue in oceanographic research. To reveal the distribution pattern of cooling water discharge of Daya Bay Nuclear Power Plant in summer and the impact on the surrounding marine environment, this research established a high-resolution three-dimensional (3D) numerical model based on ECOMSED in the Daya Bay. The model results are consistent with the observations on the distribution of tide level and temperature. The simulated horizontal distribution of temperature rise is consistent with the distribution trend of remote sensing images. The study showed that the stratification of the Daya Bay water is stronger in summer. The cooling water mainly spreads in the surface layer, and the temperature rise in the bottom layer is not apparent. Quantitative analysis showed that around 18.8-21.6 km 2 of the area has 1°C surface temperature rises. The area of temperature rises that exceeds 2 °C is between 6.2 and 8.1 km 2 . The area of temperature rises that exceeds 4 °C is between no more than 1.2 km 2 . The area with a bottom temperature rises of 1 °C does not exceed 2.2 km 2 , and there is no area that has a bottom temperature rise over 1 °C. The tidal dynamics process influences on the dispersion of cooling water discharge from Daya Bay Nuclear Power Plant, where the influence is more significant in the spring tide period than in the neap tide period. Our findings are consistent with previous researches.

Spatial distribution and risk assessment of heavy metals in seawater and sediments in Jieshi Bay, Shanwei, China - Wen Zhou; Qian Cao; Man Hong; Yutao Lei; Ding Wen; Dengfeng Zhang (Frontiers in Marine Science, 2022)
The contamination of heavy metals due to human activities has attracted great attention and may lead to serious environmental problems. This research was performed on seawater, sediments, and organisms in Jieshi Bay, China. The level of Cu, Pb, Zn, Cd, Hg, and As, respectively, was measured in each environment to acquire a comprehensive understanding of their sources and distribution and to accomplish a risk assessment. The results showed that the concentration of heavy metals in autumn was higher than those in spring, and surface water has a higher heavy metal content than bottom water. The main sources of these heavy metals could be surface runoff and industrial wastewater discharge in the said bay. Hg was the main pollutant in the seawater. Hg, Cu, Zn, and Cd could easily accumulate in organisms than other heavy metal contents. In addition, even though the concentration of Pb did not exceed the Seawater Quality Standard, decision-makers should still be attentive to the Pb content in fish because of bioaccumulation from seafood product consumption.

Exploring the interaction relationship between Beautiful China-SciTech innovation using coupling coordination and predictive analysis: a case study of Zhejiang - Yi-di Hua; Ke-man Hu; Lu-yi Qiu; Hong-an Dong; Lei Ding; Sio-Long Lo (Environment, Development and Sustainability, 2022)

The Super-large Ensemble Experiments of CAS FGOALS-g3 - Pengfei Lin; Bowen Zhao; Jilin Wei; Hailong Liu; Wenxia Zhang; Xiaolong Chen; Jie Jiang; Mengrong Ding; Wenmin Man; Jinrong Jiang; Xu Zhang; Yuewen Ding; et al. (Advances in Atmospheric Sciences, 2022)
A super-large ensemble simulation dataset with 110 members has been produced by the fully coupled model FGOALS-g3 developed by researchers at the Institute of Atmospheric Physics, Chinese Academy of Sciences. This is the first dataset of large ensemble simulations with a climate system model developed by a Chinese modeling center. The simulation has the largest realizations up to now worldwide in terms of single-model initial-condition large ensembles. Each member includes a historical experiment (1850–2014) and an experiment (2015–99) under the very high greenhouse gas emissions Shared Socioeconomic Pathway scenario (SSP5-8.5). The dataset includes monthly and daily temperature, precipitation, and other variables, requiring storage of 275 TB. Additionally, the surface air temperature (SAT) and land precipitation simulated by the FGOALS-g3 super-large ensemble have been validated and projected. The ensemble can capture the response of SAT and land precipitation to external forcings well, and the internal variabilities can be quantified. The availability of more than 100 realizations will help researchers to study rare events and improve the understanding of the impact of internal variability on forced climate changes.

Risk assessment of offshore oil spill in the northern South China Sea: A stochastic scenario modeling approach - Bingxu Geng; Wen Zhou; Lingyan Lu; Qian Cao; Man Hong; Ding Wen (Frontiers in Marine Science, 2022)
The coastal area in the northern South China Sea (nSCS) is one of China’s most economically active regions. The fast-growing industry of marine sector and the shipping has increased the probability of oil spill accidents. An oil spill is a usually unexpected incident that is harmful to the ecological environment and marine organisms of the coastal area. As a result, utilizing a numerical model to simulate the fate and transport trajectory of spilled oil and to assess the potential risk of an oil spill accident to the coastal marine environment is of great necessity. The present study aimed to examine the impact of the risk of oil spills on the coastal environment in the nSCS. We built a hydrodynamic model and an oil spill dispersion model based on MIKE21 FM to study the tidal dynamics and oil spill dispersion in the coastal area in the nSCS. Moreover, the stochastic approach was used to simulate and predict the fastest arrival time and the probability distribution of the pollution of the oil film to the surrounding environment in the coastal regions of the nSCS. We examined the mechanisms for the influences of tides and wind on the fastest arrival time of oil film and the spatial distribution of the pollution probability of oil spill incidents at different locations in the nSCS based on the model. The results showed that the wind direction has a dominating effect on the direction of the oil dispersion. Due to the differences in the tidal dynamics in different regions, the migration and dispersion of the oil are also affected by the tidal current. This research provides guidance on the risk assessment of oil spill accidents for marine environmental management.

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

The cortical organization of writing sequence: evidence from observing Chinese characters in motion - Zhaoqi Zhang; Qiming Yuan; Zeping Liu; Man Zhang; Junjie Wu; Chunming Lu; Guosheng Ding; Taomei Guo (Brain Structure and Function, 2021)

Patterns and networks of language control in bilingual language production - Qiming Yuan; Junjie Wu; Man Zhang; Zhaoqi Zhang; Mo Chen; Guosheng Ding; Chunming Lu; Taomei Guo (Brain Structure and Function, 2021)

Fetal growth, fetal development, and placental features in women with polycystic ovary syndrome: analysis based on fetal and placental magnetic resonance imaging - Qing Zhang; Zhong-kun Bao; Mei-xiang Deng; Qiong Xu; Dan-dan Ding; Man-man Pan; Xi Xi; Fang-fang Wang; Yu Zou; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2020)

Monitoring thermal field, humidity field and energy balance over heterogeneous surfaces in the typical valley-city - Guodong Li; Junhua Zhang; Parham A. Mirzaei; Shengyan Ding; Yapeng Ding; Man Liu (Journal of Geographical Sciences, 2020)

Transcriptional profiling analysis of OsDT11-mediated ABA-dependent signal pathway for drought tolerance in rice - Man Zhao; Yanhu Ju; Bo Zhao; Xiaoming Li; LIli Dai; Jicheng Qu; Zhaohui Chu; Xinhua Ding (Plant Biotechnology Reports, 2020)

The comparison of transcriptomic response of green microalga Chlorella sorokiniana exposure to environmentally relevant concentration of cadmium(II) and 4-n-nonylphenol - Na Ding; Lu Wang; Yuan Kang; Kesong Luo; Diya Zeng; Yu Bon Man; Qiuyun Zhang; Lixuan Zeng; Jiwen Luo; Feng Jiang (Environmental Geochemistry and Health, 2020)

Vanadium compounds induced damage of human umbilical vein endothelial cells and the protective effect of berberine - Cong-Cong Hou; Hong-Yu Liang; Yi-Hui Pan; Man Wang; Li-Li Zhao; Yuan Bian; Duan-Yuan Cao; Ding Zhao (BioMetals, 2019)

Design, synthesis, bioactivity, and DFT calculation of 2-thiazolyl-hydrazone derivatives as influenza neuraminidase inhibitors - Man-Ying Cui; Jian-Xia Nie; Zhong-Zhong Yan; Meng-Wu Xiao; Ding Lin; Jiao Ye; Ai-Xi Hu (Medicinal Chemistry Research, 2019)

Cellular stress and redox activity proteins are involved in gastric carcinogenesis associated with Helicobacter pylori infection expressing high levels of thioredoxin-1 - Yan-yan Shi; Jing Zhang; Ting Zhang; Man Zhou; Ye Wang; He-jun Zhang; Shi-gang Ding (Journal of Zhejiang University-SCIENCE B, 2018)

Ferrovibrio xuzhouensis sp. nov., a cyhalothrin-degrading bacterium isolated from cyhalothrin contaminated wastewater - Man Song; Long Zhang; Bin Sun; Hao Zhang; Hui Ding; Qiang Li; Suhui Guo; Xing Huang (Antonie van Leeuwenhoek, 2015)

Analysis of an antennal cDNA library and the expression patterns of two olfactory genes in Frankliniella occidentalis (Thysanoptera: Thripidae) - Fang-Fang Zeng; Shuang-Shuang Zhou; Yan-Hong Ding; Man-Qun Wang (Applied Entomology and Zoology, 2015)

The Levels of Ki-67 Positive are Positively Associated with Lymph Node Metastasis in Invasive Ductal Breast Cancer - Yongxiang Yin; Ke Zeng; Man Wu; Yun Ding; Min Zhao; Qi Chen (Cell Biochemistry and Biophysics, 2014)

Fluid Flow-Induced Calcium Response in Osteoclasts: Signaling Pathways - Ping Li; Chenglin Liu; Man Hu; Mian Long; Ding Zhang; Bo Huo (Annals of Biomedical Engineering, 2014)

A Novel Colorimetric and Off–On Fluorescent Chemosensor for Cr3+ in Aqueous Solution and its Application in Live Cell Imaging - Man Li; Di Zhang; Yaqi Liu; Peigang Ding; Yong Ye; Yufen Zhao (Journal of Fluorescence, 2014)

Molecular characteristics and evolutionary analysis of field Marek’s disease virus prevalent in vaccinated chicken flocks in recent years in China - Zu-Hua Yu; Man Teng; Jun Luo; Xin-Wei Wang; Ke Ding; Le-Le Yu; Jing-Wei Su; Jia-Qi Chi; Pu Zhao; Bo Hu; Gai-Ping Zhang; Ju-Xiong Liu (Virus Genes, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Combined Effects of PFOS and PFOA on Zebrafish (Danio rerio) Embryos - Guanghui Ding; Jing Zhang; Yihong Chen; Luyan Wang; Man Wang; Deqi Xiong; Yeqing Sun (Archives of Environmental Contamination and Toxicology, 2013)

Fluid Flow-Induced Calcium Response in Early or Late Differentiated Osteoclasts - Ping Li; Man Hu; Shujin Sun; Yan Zhang; Yuxin Gao; Mian Long; Bo Huo; Ding Zhang (Annals of Biomedical Engineering, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

Changes to the groundwater system, from 1888 to present, in a highly-urbanized coastal area in Hong Kong, China - Jiu Jimmy Jiao; Chi-man Leung; Guoping Ding (Hydrogeology Journal, 2008)